Edge‐Site‐Free and Topological‐Defect‐Rich Carbon Cathode for High‐Performance Lithium‐Oxygen Batteries - Wei Yu; Takeharu Yoshii; Alex Aziz; Rui Tang; Zheng‐Ze Pan; Kazutoshi Inoue; Motoko Kotani; Hideki Tanaka; Eva Scholtzová; Daniel Tunega; Yuta Nishina; Kiho Nishioka; et al. (Advanced Science, 2023)
Abstract The rational design of a stable and catalytic carbon cathode is crucial for the development of rechargeable lithium‐oxygen (LiO2) batteries. An edge‐site‐free and topological‐defect‐rich graphene‐based material is proposed as a pure carbon cathode that drastically improves LiO2 battery performance, even in the absence of extra catalysts and mediators. The proposed graphene‐based material is synthesized using the advanced template technique coupled with high‐temperature annealing at 1800 °C. The material possesses an edge‐site‐free framework and mesoporosity, which is crucial to achieve excellent electrochemical stability and an ultra‐large capacity (>6700 mAh g−1). Moreover, both experimental and theoretical structural characterization demonstrates the presence of a significant number of topological defects, which are non‐hexagonal carbon rings in the graphene framework. In situ isotopic electrochemical mass spectrometry and theoretical calculations reveal the unique catalysis of topological defects in the formation of amorphous Li2O2, which may be decomposed at low potential (∼ 3.6 V versus Li/Li+) and leads to improved cycle performance. Furthermore, a flexible electrode sheet that excludes organic binders exhibits an extremely long lifetime of up to 307 cycles (>1535 h), in the absence of solid or soluble catalysts. These findings may be used to design robust carbon cathodes for LiO2 batteries.